FPR1, as a Potential Biomarker of Diagnosis and Infliximab Therapy Responses for Crohn’s Disease, is Related to Disease Activity, Inflammation and Macrophage Polarization - Ye C; Zhu S; Yuan J; Yuan X (Dove Medical Press, 2024)
Chenglin Ye,1,* Sizhe Zhu,2,* Jingping Yuan,1 Xiuxue Yuan3 1Department of Pathology, Renmin Hospital of Wuhan University, Wuhan, Hubei, People's Republic of China; 2Department of Otolaryngology-Head and Neck Surgery, Tongji Hospital, Tongji Medical College, Huazhong University of Sciences and Technology, Wuhan, Hubei, People's Republic of China; 3Medical College of Wuhan University of Science and Technology, Wuhan, Hubei, People's Republic of China*These authors contributed equally to this workCorrespondence: Jingping Yuan; Xiuxue Yuan, Email yuanjingping@whu.edu.cn; exiuwust@gmail.comPurpose: Crohn's disease (CD) represents a multifaceted inflammatory gastrointestinal condition, with a profound significance placed on unraveling its molecular pathways to enhance both diagnostic capabilities and therapeutic interventions. This study focused on identifying a robust macrophage-related signatures (MacroSig) for diagnosing CD, emphasizing the role of FPR1 in macrophage polarization and its implications in CD.Patients and Methods: Expression profiles from intestinal biopsies and macrophages of 1804 CD patients were retrieved from the Gene Expression Omnibus (GEO). Utilizing CIBERSORTx, differential expression analysis, and weighted correlation network analysis to to identify macrophage-related genes (MRGs). By unsupervised clustering, distinct clusters of CD were identified. Potential biomarkers were identified via using four machine learning algorithms, leading to the establishment of MacroSig which combines insights from 12 machine learning algorithms. Furthermore, the expression of FPR1 was verified in intestinal biopsies of CD patients and two murine experimental colitis models. Finally, we further explored the role of FPR1 in macrophage polarization through single-cell analysis as well as through the study of RAW264.7 cells and peritoneal macrophages.Results: Two distinct clusters with differential levels of macrophage infiltration and inflammation were identified. The MacroSig, which included FPR1 and LILRB2, exhibited high diagnostic accuracy and outperformed existing biomarkers and signatures. Clinical analysis demonstrated a strong correlation of FPR1 with disease activity, endoscopic inflammation status, and response to infliximab treatment. The expression levels of FPR1 were validated in our CD cohort by immunohistochemistry and confirmed in two colitis mouse models. Single-cell analysis indicated that FPR1 is predominantly expressed in macrophages and monocytes. In vitro studies demonstrated that FPR1 was upregulated in M1 macrophages, and its activation promoted M1 polarization.Conclusion: We developed a promising diagnostic signature for CD, and targeting FPR1 to modulate macrophage polarization may represent a novel therapeutic strategy.Keywords: Crohn's disease, macrophage, diagnostic signature, FPR1, machine learning